Gottes Triumph und die Aufgabe des Apostels. Überlegungen zu 2Kor 2,14 - Koch, Dietrich-Alex 1942- (2018)
The notion of thriambeúein (accompanied by an accusative) in 2Cor 2:14 is heavily disputed (NRSV: But thanks be to God, who in Christ always leads us in triumphal procession). Judging from the use in military contexts Paul would say that God is leading him around as his defeated enemy. But the literary context of 2Cor 2:14 does not support this reading. On the other hand here thriambeúein is used metaphorically of a divine procession. If we take into account the iconography of divine triumphal processions (of Dionysos, Neptun) we see a great flexibility in the presentation, even without enemies and soldiers. Therefore it is necessary to look for the special context in 2Cor2:14: By using the metaphor of the divine triumph Paul emphasizes the importance of God's action for his apostolic work – and this work is described by a second metaphor, the metaphor of fragrance (osmé) and aroma (euodía). On the literary level Paul uses both metaphors to prepare the question: “And who is qualified for these things?”, and this question is the subject of 2Cor 2:14–7:4.
Keywords: Pauline Theology; 2 Cor